Cognitive Aspects of Comb-Building in the Honeybee? - Gallo, Vincent; Chittka, Lars (Frontiers in Psychology, 2018)
The wax-made comb of the honeybee is a masterpiece of animal architecture. The highly regular, double-sided hexagonal structure is a near-optimal solution to storing food and housing larvae, economizing on building materials and space. Elaborate though they may seem, such animal constructions are often viewed as the result of ‘just instinct’, governed by inflexible, pre-programmed, innate behavior routines. An inspection of the literature on honeybee comb construction, however, reveals a different picture. Workers have to learn, at least in part, certain elements of the technique, and there is considerable flexibility in terms of how the shape of the comb and its gradual manufacture is tailored to the circumstances, especially the available space. Moreover, we explore the 2-century old and now largely forgotten work by François Huber, where glass screens were placed between an expanding comb construction and the intended target wall. Bees took corrective action before reaching the glass obstacle, and altered the ongoing construction so as to reach the nearest wooded wall. Though further experiments will be necessary, these results suggest a form of spatial planning skills. We discuss these findings in the context of what is now known about insect cognition, and ask if it is possible that the production of hexagonal wax combs is the result of behavioral heuristics where a complex structure emerges as the result of simple behavioral rules applied by each individual, or whether prospective cognition might be involved.